Pengaruh Kompetensi Widyaiswara Terhadap Prestasi Peserta Diklat Pada Matadiklat Etika Publik di Pusdiklat BPS - Utama Andri Arjita (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
The purpose of the research is to see what variables exist in widyaiswara competencies which influence their performance as training participants. This is a quantitative approach with analytical methods in the form of analytical statistics. The analysis technique is multiple linear regression. The results of the analysis shows that not all variables in widyaiswara competencies affect the training participants' performance. Competence that has a direct influence is the competence of systematic presentation, presentation ability, and answering questions. Personality competency and social competence are not influential on the performance of participants.